Influence of agricultural extension services on technical efficiency of maize farmers in Malawi - Jolex, Aubrey (African Association of Agricultural Economists, 2022)
Recognising potential selection bias due to non-randomness of the data, this study used propensity score matching on data from a nationally representative fifth Integrated Household Survey (IHS5) to investigate the effect of agriculture extension services on the technical efficiency of maize farmers in Malawi. Technical efficiency levels were estimated using the stochastic frontier model. The results show that most farmers are technically efficient, with an average technical efficiency of 63%. This indicates that there is still a possibility to increase maize output by 37% using the same level of inputs. The results of the propensity score matching reveal that having access to agricultural extension services significantly increases maize farmers’ technical efficiency, by about 4%. This evidence presents an opportunity not only for farmers, but also for the relevant policymakers, to realise the potential of using agricultural extension services to enhance the production capacity of maize farmers.